'An oasis of freedom' in communist Poland: The horse racetrack in Warsaw in the memory of its regular visitors. (December 2020) - Bossak-Herbst, Barbara; Głowacka-Grajper, Małgorzata
In this article the memory narrations of regular visitors to the Służewiec Racetrack in Warsaw are analysed. This, the only one long-term operating horse racetrack in communist Poland, was an enclave within public space, called by racegoers, who are predominantly elderly men, an 'oasis of freedom' – distant from the everyday reality and the rules of the official socialist ideology. The intricacies of the memory of regular racegoers are considered in reference to a broader discussion on the phenomenon of 'post-communist nostalgia'. The nostalgic narrations are not only connected with communism but also with the imaginations of inter-war period's horseracing. The authors show that contemporary interpretations of the horseracing world in communist Poland in terms of a 'paradise lost' expresses not positive assessing of the past but rather the criticism of post-communist times, when Polish horseracing has impoverished. Although the betting pools are now low, the ritualized gambling, practiced within the space of the Warsaw racetrack, seems to restore among the regular racegoers a sense of being in contact with that past better world.